2021
DOI: 10.3390/app112210598
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement and Improved Mechanical Properties of EUROFER97 by Thermo-Mechanical Treatments

Abstract: EUROFER97 steel plates for nuclear fusion applications are usually manufactured by hot rolling and subsequent heat treatments: (1) austenitization at 980 °C for 30 min, (2) rapid cooling and (3) tempering at 760 °C for 90 min. An extended experimental campaign was carried out with the scope of improving the strength of the steel without a loss of ductility. Forty groups of samples were prepared by combining cold rolling with five cold reduction ratios (20, 40, 50, 60 and 80%) and heat treatments at eight diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…It is also successfully applied after cold rolling to promote grain refinement [27,28], leading to an increase in tensile properties [29][30][31]. It is reported that the application of UFH inhibits the dislocation re-organization which is typical of recovery [32][33][34][35]. Hence recrystallization process occurs in direct competition with austenitization [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…It is also successfully applied after cold rolling to promote grain refinement [27,28], leading to an increase in tensile properties [29][30][31]. It is reported that the application of UFH inhibits the dislocation re-organization which is typical of recovery [32][33][34][35]. Hence recrystallization process occurs in direct competition with austenitization [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…During the subsequent annealing heat treatment, following the work-hardening induced by the deformation process, primary recrystallization and grain growth phenomena occur, depending on the heat treatment temperature and soaking time [51,52]. The grain growth phenomena typically act in two modes: (I) normal grain growth (NGG) with a uniform increase in grain size, based on grain boundary migration and annihilation of slam grains; (II) abnormal grain growth (AGG) or secondary recrystallization, characterized by the rapid growth of some grains at the expense of neighboring ones (e.g., [53,54]).…”
Section: Introductionmentioning
confidence: 99%
“…The development of high strength materials for oil and gas and energy application has been driven in last times by customer requests to combine high tensile properties, impact resistance and good weldability on industrial scale at prices responding to market requests [1][2][3][4][5]. A comparable figure is met in different market sectors of structural steels (for example offshore metallic structures or ships, with broadly similar aims).…”
Section: Introductionmentioning
confidence: 99%